2014
DOI: 10.1007/s11629-013-2707-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and recovery of soil nitrogen by bryophytes and vascular plants in an alpine meadow

Abstract: Due to their particular physiology and life history traits, bryophytes are critical in regulating biogeochemical cycles and functions in alpine ecosystem. Hence, it is crucial to investigate their nutrient utilization strategies in comparison with vascular plants and understand their responses to the variation of growing season caused by climate change. Firstly, this study testified whether or not bryophytes can absorb nitrogen (N) directly from soil through spiking three chemical forms of 15N stable isotope t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…These results suggest that moss NO 3 − uptake and accumulation is less a function of species identity, but it is rather more significantly influenced by environmental NO 3 − availability. This finding on moss NO 3 − uptake is consistent with that of tracer studies, which showed that the concentrations of applied 15 NO 3 − in mosses did not differ significantly between species, but they did differ significantly between doses of 15 NO 3 − applications or sites with different levels of atmospheric N deposition (Ayres et al, 2006; Wang et al, 2014; Wiedermann et al, 2009). In contrast, Wanek and Pörtl (2008) found that the kinetic constants of 15 NO 3 − uptake differed significantly between moss species, but not between bryophytes colonizing different microhabitats.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results suggest that moss NO 3 − uptake and accumulation is less a function of species identity, but it is rather more significantly influenced by environmental NO 3 − availability. This finding on moss NO 3 − uptake is consistent with that of tracer studies, which showed that the concentrations of applied 15 NO 3 − in mosses did not differ significantly between species, but they did differ significantly between doses of 15 NO 3 − applications or sites with different levels of atmospheric N deposition (Ayres et al, 2006; Wang et al, 2014; Wiedermann et al, 2009). In contrast, Wanek and Pörtl (2008) found that the kinetic constants of 15 NO 3 − uptake differed significantly between moss species, but not between bryophytes colonizing different microhabitats.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the average Φ soil values based on natural isotopes (equations and ) were 53 ± 13% (Figures 4a and 4b). Previously, the average fraction of soil‐derived N was determined to be 10% in a short‐term study (7 days) of mat‐forming mosses using labeled 15 N‐NO 3 − : 15 N‐NH 4 + (1:1) additions (Ayres et al, 2006), and the mean fractions of 15 N tracer recovery in the mosses from the 15 N‐NO 3 − spiked soils of an alpine meadow were 17–30% (Wang et al, 2014). These fractional contribution values cannot be directly compared due to differences in the methods used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies were performed in relatively stable ecosystems, whereas BSCs proceed from early to late succession stages over long time periods. BSCs make up an important component of all alpine meadow ecosystems (Wang et al 2014), but the BSC type and coverage changes with alpine meadow succession . BSCs in alpine meadows are a special case, because they are the result of intensive land use, especially overgrazing, and alpine meadow is fine-textured.…”
Section: Introductionmentioning
confidence: 99%